(untitled) (Revista Contexto & Saúde, 2025)
This study evaluated the in vivo giardicidal potential of black tea (Camellia sinensis) in male Swiss mice experimentally infected with 104 cysts of Giardia duodenalis assemblage BIV. The animals were assigned to nine groups and treated with filtered water (GC+), metronidazole (MT, 500 mg/kg/day), black tea (CP) at 100, 150, or 200 mg/kg/day, or combinations of CP with MT. A negative control group (GC−) included uninfected animals receiving filtered water. Treatments were administered for seven days, and infection status was assessed through parasitological analysis and Polymerase Chain Reaction (PCR). CP at 200 mg/kg induced complete elimination of G. duodenalis, while doses of 100 and 150 mg/kg reduced parasite load from high to medium and low levels, respectively. MT alone did not result in cure but reduced parasite burden. The combination of MT with any CP dose achieved full parasite clearance, indicating a synergistic effect. These results demonstrate a dose-dependent giardicidal effect of black tea and suggest that its combination with metronidazole enhances treatment efficacy. The findings reinforce the therapeutic potential of phytotherapeutics as effective, low-cost adjuncts in the management of giardiasis. From a health promotion perspective, the identification of natural antiparasitic compounds supports the development of accessible and sustainable treatment strategies. This is particularly relevant in resource-limited settings, where conventional therapies may be less accessible or poorly tolerated. Further research, including clinical trials and mechanistic studies, is warranted to explore the broader applicability of these combinations in human populations.